The Periotome as a Tool for Atraumatic Tooth Extraction – A Review of the Literature - Wdowiak, Natalia; Czerepak, Gabriela; Jaruga, Paulina; Jachimczuk, Ewa; Bednarz, Katarzyna; Smyczyńska, Natalia (Quality in Sport, 2026)
Background: The rapid advancement of implantology necessitates the use of extraction methods that preserve bone tissue. Aim: The objective of this study is to review the literature on periotomes as tools for atraumatic tooth extraction, evaluate their clinical benefits, and assess periotome models currently available on the market. Materials and methods: A review of the available scientific literature from the years 2004-2025 was conducted to evaluate the clinical application of periotomes, and their impact on alveolar bone preservation and implant treatment outcomes. Results: Periotomes allow practitioners to precisely severe the periodontal ligament, minimizing trauma to the bone and soft tissues. Unlike traditional methods, they do not require forceful luxation. Studies show that their use is associated with less bone loss than with piezotomes and faster wound healing. These instruments come in many variants (straight, curved, titanium), allowing them to be adapted to the tooth’s morphology. Conclusions: The use of periotomes is an efficient and cost-effective method for preserving the alveolar ridge. These instruments reduce post-operative pain and are essential for preparing the implant site, offering a safe alternative to more invasive techniques.